Field dependent study on formation of ferroelectric domain in KNbO3 single crystal - et. al., Vivek B. Korde, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study of ferroelectric domains is essential for understanding the orientation of electric dipoles. This orientation of electric dipole shows the defect and impurities formation in a ferroelectric single crystal. Domain study is important for studying formations of defects and movement of dipoles in Al-doped KNbO3 single crystal. The Al-doped KNbO3 ferroelectric Single-crystal prepared using flux methods; then it chemically etched using methyl alcohol and nitric acid as an etchant. The electric field of 50 V/cm, 60 V/cm, and 70 V/cm was applied to the doped crystal. The variations of domain structure after the applying electric field are observed using the Trinocular microscopy method